Nasihat nasihat C. Snouck Hurgronye semasa kepegawaian kepada pemerintah Hindia Belandas 1889- 1936 - E. Gobee (INIS, 1995)
ws.jl.1-11c.1/ir, jil.3,c.2-6 ; jil.11,c.2-6/an, jil.8=c.2/oen, jil.8, c.3-6